Reallocation, productivity, and monetary policy in an energy crisis - Boris Chafwehé; Andrea Colciago; Romanos Priftis (European Central Bank (ECB), 2024)
This paper introduces a New Keynesian multi-sector industry model that integrates firm heterogeneity, entry, and exit dynamics, while considering energy production from both fossil fuels and renewables. We investigate the effects of a sustained increase in fossil fuel prices on sectoral size, labor productivity, and inflation. A hike in the price of fossil resources results in higher energy prices. Due to ex-ante heterogeneity in energy intensity in production, the profitability of sectors is impacted asymmetrically. As production costs rise, less efficient firms leave the market, while new entrants must display higher idiosyncratic productivity. While this process enhances average labor productivity, it also results in a lasting decrease in the entry of new firms. A central bank with a strong anti-inflationary stance can circumvent the energy price increase and mitigate its inflationary effects by curbing rising production costs. This policy entails a higher impact cost in terms of output and lower average productivity, but leads to a faster recovery in business dynamism. Thus, our results suggest that monetary policy faces a trade-off between stabilizing aggregate activity and business dynamism.
Keywords: E62; L16; O33; Q43; 330; Energy; productivity; firm entry and exit; monetary policy